Jing Guan Fang, an herbal formula, as an immunomodulator: opposing effects on basal and lipopolysaccharide-induced inflammation of macrophage via JAK/STAT3 and MAPK pathways - Lin, Zhi-Hu; Yeh, Hsin; Phan, Sang-Nguyen-Cao; Liao, Li-Lan; Chen, Chien-Chang; Hsu, Wei-Hung; Hsu, Chung-Hua; Lin, Tung-Yi (Frontiers in Pharmacology, 2025)
Jing Guan Fang, a formula based on Forsythia suspensa, is commonly used for preventing SARS-CoV-2 infection and alleviating cold-like symptoms. However, the precise immunoregulatory mechanisms underlying its effects remain unclear and warrant investigation. This study aims to investigate the immunomodulatory effects of JGF and further elucidate the underlying mechanisms. The results showed that JGF had minimal impact on the cell viability of RAW264.7 and MH-S. In the absence of LPS stimulation, JGF promoted macrophages to produce NO and pro-inflammatory cytokines in a concentration-dependent manner. However, after LPS treatment, the JGF add-on exhibited contrasting effects, with the half-maximal effective concentrations for reducing macrophage-secreted NO and IL-6 being 80 and 180 μg/mL, respectively. Western blot analysis revealed that the JGF supplement marginally induced the production of iNOS and COX-2 without LPS stimulation. However, in LPS-pretreated cells, JGF demonstrated the opposite effect. JGF monotherapy accelerated phosphorylation in the JNK and JAK2 signaling pathways. In contrast, JGF inhibited LPS-stimulated STAT3 phosphorylation by suppressing JNK1/2 activation. Moreover, JGF reduced LPS-induced expression of IL-6 and TNF-α in the lungs and serum of mice. Collectively, the findings suggest that JGF exhibits immunomodulatory activity and suppresses pro-inflammatory cytokine expression caused by LPS.